CLINICAL SIGNIFICANCE OF TP53 ABERRATIONS AND IGHV MUTATIONAL STATUS IN CHRONIC LYMPHOCYTIC LEUKEMIA - Tomic, Kristina; Karan Djurasevic, Teodora; Vukovic, Vojin; Mihaljevic, Biljana; Antic, Darko (Medicinski podmladak, 2020)
Chronic lymphocytic leukemia (CLL) is a very heterogeneous disease with a variable clinical course. On the one side of the spectrum we have patients with aggressive and resistant disease, of which they die only a few months after diagnosis while, on the other side, there are patients with an indolent, slowly progressive disease that does not require treatment for decades. The reasons for this are only partially known, but they have been the subject of numerous scientific studies during the last several decades. Consequently, the concept of prognostic and predictive factors in CLL have emerged, which aims to predict the clinical course and therapeutic outcome of CLL. With the improvement of understanding the pathophysiology of this disease, the lists of prognostic and predictive factors are getting longer every year, but they also overlap. In this review, we singled out the aberrations of the TP53 gene and the IGHV (immunoglobulin heavy variable) gene mutational status as the two most important and most studied factors that have both prognostic and predictive significance.
Keywords: chronic lymphocytic leukemia, TP53 aberrations, IGHV mutational status